Meta Analisis: Deferensiasi Gaya Belajar dengan Metode Pembelajaran - A. Jauhar Fuad (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2016)
This paper intends to review with the student's learning style dimensions of divergent and convergent. Both interact with the methods of debate and methods of discussion. Differences in learning styles impact on student learning, student learning outcomes specify a maximum learning. Therefore, teachers need to understand the learning style that is owned by the students, before applying the learning method that will be chosen. This paper concludes convergent learning style has a stronger interaction with the method of debate while the divergent learning style has a stronger interaction with the method of discussion